Characterization of the adherence strength and the aggregate-paste bond of prestressed concrete with siderurgical aggregates. (15th August 2022) - Tamayo, P.; Aghajanian, A.; Rico, J.; Setién, J.; Polanco, J.A.; Thomas, C.
Abstract: Concrete with siderurgical aggregates (SA) is a sustainable construction material with great potential as structural concrete. For this reason, studies must be carried out on the behavior of concrete against prestressed elements, studies that open the door to new applications such as buildings, bridges or foundations. In this study, the feasibility of prestressed concrete is established with standardized adherence tests on beams reinforced with steel wires. The comparison between the concrete-reinforcement union of limestone concrete and concrete with siderurgical aggregates, has shown to be 23% higher in the case of the latter. This study is completed with the analysis of the paste-aggregate interface (ITZ) of both types of aggregate to support the results obtained in the adherence test. In addition, in order to know the bond strength of the pastes that incorporate SA, the micro-Vickers hardness of the pastes of the concrete mixes are determined, a hardness that has turned out to be proportional to the replacement of fine aggregates with SA. Highlights: A comprehensive analysis of the siderurgical aggregate concrete were compiled through a critical literature review. ITZ of concrete with siderurgical aggregates is less porous. Microhardness of the pastes is 55% higher in siderurgical concrete. A better concrete-reinforcement bonding with the siderurgical aggregate is observed.